De pai para filho: um estudo da produção antroponômica do trabalhador canavieiro alagoano - Santos, Charles dos (2013)
The purpose of this research is to shed light on the process of insertion and socialization of rural workers in the sugarcane industry from Alagoas. For this, we make use of the concept of antroponomia, coined by the French sociologist Daniel Bertaux, and that try to relate the stages of production of goods to production of people. We seek on the next pages analyze critically the historical facts that led whole families to lose their condition as moradores and smallholders and to have to sell its workforce to the sugar mills and alcohol installed in the region of the tabuleiros, where they carry out services underpaid and in many cases of unworthy way. It is our intent to observe the manner in which the peasant gave way to the rural proletariat and how occurred - and occurs- the production of new workers, often children and grandchildren of those who were expelled from the morada and proletarianized. The places we elect as locus of empirical immersion were the cities of Teotônio Vilela/AL and Pilar/AL, where we interviewed cane cutters, irrigation workers, herbicide applicators and administrators, among other agents. The data collection techniques used were the life history and the semi-structured interview.